Correction: Use of the Puccinia sorghi haustorial transcriptome to identify and characterize AvrRp1-D recognized by the maize Rp1-D resistance protein. - PLOS Pathogens Staff (PLoS Pathogens)
[This corrects the article DOI: 10.1371/journal.ppat.1012662.].